Environmental controls on intragroup diversity of the uncultured benthic archaea of the miscellaneous Crenarchaeotal group lineage naturally enriched in anoxic sediments of the White Oak River estuary (North Carolina, USA). (30th January 2015) - Lazar, Cassandre Sara; Biddle, Jennifer F.; Meador, Travis B.; Blair, Nic; Hinrichs, Kai‐Uwe; Teske, Andreas P.
Summary Sediments of the White Oak River (WOR) estuary are situated on the coast of North Carolina harbour, one of the most diverse known populations of uncultured Archaea, specifically the miscellaneous Crenarchaeotal group (MCG). In order to constrain the environmental factors influencing the uncultured archaeal groups in the WOR estuary, biogeochemical profiles as well as archaeal 16S rRNA genes from sediment pushcores were analysed. The relative fraction of MCG Archaea in clone libraries decreased at shallow sediment depths (27% of the total MCG). A LINKTREE analysis of the MCG intragroup diversity reinforced the observation that the MCG subgroup 6 was found predominantly within sulfide‐depleted shallow sediment layers; other subgroups (especially MCG‐1 and MCG‐5/8) occurred preferentially in deeper, more strongly reducing sediment layers. The available evidence from this study and published MCG distribution patterns indicates that the MCG‐6 subgroup is a specialized MCG lineage that, in contrast to other MCG subgroups, prefers suboxic sediment horizons with minimal or no free sulfide. Collectively, our results reveal the habitat preferences of different MCG subgroups in the WOR sediments and suggest that physiological adaptations to distinct sedimentary geochemical niches evolved in different MCG subgroups.